Functional evaluation of fluorescein-labeled derivatives of a peptide inhibitor of the EGF receptor dimerization. Issue 16 (15th August 2016) - Toyama, Kei; Mizuguchi, Takaaki; Nomura, Wataru; Tamamura, Hirokazu
Graphical abstract: Abstract: A cyclic decapeptide (1, ), which acts on the extracellular region of the EGF receptor, preventing it from dimerizing, has been developed. Peptide2, which was labeled with fluorescein at the N-terminus of peptide1, was synthesized based on structure–activity relationship studies. Peptide2 essentially retained the inhibitory activity of peptide1 against the receptor autophosphorylation. Confocal microscopy studies revealed that in carcinoma cells, the fluorescence of peptide2 was localized inside some vesicles. Treatment of intact cells by peptide1 in combination with peptide2 decreased the fluorescence intensity significantly compared to treatment with only peptide2 . These results indicate that peptide2 competes with peptide1 for binding to the cellular surface. Six derivatives of peptide2, in which constituent amino acids, with the exception of two cysteines and proline were randomized, were synthesized and used to treat the cells. Peptides6 and9 showed the highest fluorescence intensity in cells. From the results of the EGF receptor autophosphorylation assay, these two derivatives were proven to have higher inhibitory activity than peptide2, which would therefore be a useful delivery peptide and fluorescent probe to find new inhibitors against the EGF receptor. Peptides6 and9 are promising leads for EGF receptor inhibitors.